The structure of international environmental agreements - Carlo Carraro (Fondazione Eni Enrico Mattei (FEEM), 1998)
Since the framework convention of Rio, actual environmental negotiations on climate change aim at inducing all world countries to sign global environmental agreements to reduce greenhouse gas emissions. Despite the past unsuccessful attempts, even current negotiations seem to pursue the same objective. This paper shows from a game-theoretic viewpoint that the emergence of agreements signed by all countries is quite unlikely, even in the presence of appropriate and multi-issues negotiation strategies and transfers. Either a single partial agreement or a coalition structure in which regional environmental agreements to control climate change are signed are the most likely outcomes. The paper compares these two cases and argues that regional agreements may increase both countries welfare and environmental quality.
Keywords: C72; H41; Q40; Q48; 330; Non-cooperative game theory; Endogenous formation of coalitions; Environmental agreements; Climate change; Umweltabkommen; Spieltheorie; Theorie